Porous Gold with a Nested‐Network Architecture and Ultrafine Structure. (16th March 2015) - Qi, Zhen; Vainio, Ulla; Kornowski, Andreas; Ritter, Martin; Weller, Horst; Jin, Haijun; Weissmüller, Jörg
<x xml:space="preserve">Abstract</x> A preparation strategy is developed for monolithic samples of nanoporous gold with a hierarchical structure comprising two nested networks of solid "ligaments" on distinctly different structural length scales. The electrochemical dealloying protocol achieves a large retention of less noble element in a first corrosion step, thereby allowing an extra corrosion step which forms a separate structural hierarchy level. The beneficial impact of adding Pt to the Ag–Au master alloys that are more conventionally used in dealloying approaches to nanoporous gold is demonstrated. At ≈6 nm, the lower hierarchy level ligament size emerges extremely small. Furthermore, Pt favors the retention of Ag during the first dealloying step even when the master alloy has a high Au content. The high Au content reduces the corrosion‐induced shrinkage, mitigating crack formation during preparation and favoring the formation of high‐quality macroscopic (mm‐sized) samples. The corrosion effectively carves out the nanoscale hierarchical ligament structure from the parent crystals tens of micrometers in size. This is revealed by X‐ray as well as electron backscatter diffraction, which shows that the porous crystallites inherit the highly ordered, macroscopic crystal lattice structure of the master alloy.